Chronic tendinitis versus tendinosis in podiatric pathology. Cytological and histological update - Rodríguez Sanz, David; Cerdeño Arconada, José David (Revista Internacional de Ciencias Podológicas, 2011)
Largely about injuries that appears in our feet, we can find into the tendinous structure, so its really necessary to refresh the knowledge about tendon structure an tissues. Below, we´ll do a review so we can get the new ideas about injuries tendon so it helps us to improve our aetiology diagnosis and treatments that we do in our clinical activity.